2021
DOI: 10.1186/s12882-021-02407-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between physical activity and mortality in end-stage kidney disease: a systematic review of observational studies

Abstract: Background End-stage Kidney Disease patients have a high mortality and hospitalization risk. The association of these outcomes with physical activity is described in the general population and in other chronic diseases. However, few studies examining this association have been completed in end-stage Kidney Disease patients, raising the need to systematically review the evidence on the association of physical activity with mortality and hospitalization in this population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 46 publications
4
25
0
Order By: Relevance
“…In general, the more severely reduced the glomerular filtration rate (GFR), the more physically inactive [ 1 , 43 , 50 ] and the more severely impaired the exercise capacity of many CKD patients [ 37 , 46 ]. These matters are considered to be of major clinical importance because physical dysfunction, muscle atrophy, and reduced muscle strength are all associated with poor quality of life and increased morbidity and mortality in CKD and ESRD patients [ 4 , 6 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Physical Inactivity and Physical Function In Ckd Patientsmentioning
confidence: 99%
“…In general, the more severely reduced the glomerular filtration rate (GFR), the more physically inactive [ 1 , 43 , 50 ] and the more severely impaired the exercise capacity of many CKD patients [ 37 , 46 ]. These matters are considered to be of major clinical importance because physical dysfunction, muscle atrophy, and reduced muscle strength are all associated with poor quality of life and increased morbidity and mortality in CKD and ESRD patients [ 4 , 6 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Physical Inactivity and Physical Function In Ckd Patientsmentioning
confidence: 99%
“…Substantial prospective observational studies of HD patients support the same conclusion ( Table 1 ). In a recent meta-analysis of nine cohort studies, greatest vs. lowest physical activity levels was associated with a 14% lower risk of all-cause mortality (hazard ratio (HR) = 0.86, 95% confidence interval ( CI ), 0.83 to 0.89; P = 0.003) in patients with end-stage renal disease ( 23 ). Data from the Dialysis Outcomes and Practice Patterns Study (DOPPS) revealed that mortality risk was lower among patients who engage in regular physical activity (HR = 0.73, 95% CI , 0.69 to 0.78; P < 0.001) ( 24 ).…”
Section: Physical Activity and Mortality: Data From Cohort Studiesmentioning
confidence: 99%
“…Collectively, large epidemiological studies and several randomized controlled trials, including both the general population and those with CKD, provide evidence that increased physical activity can reduce the risk of mortality [ 117 120 ]. The recommendations for frequency, intensity, time, and type of exercise are still being developed for those with CKD [ 121 ].…”
Section: Weight Loss Interventions and Kidney Function In Adpkdmentioning
confidence: 99%